FINANCIAL SLACK AND VOLUNTARY REPORTING ON STOCK DECISION: EXPERIMENTAL STUDY - Jesica Handoko; Sihar Tigor B. Tambunan; Ceicilia Bintang Hari Yudhanti (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2024)
The high increase in the number of young investors in the Indonesian capital market encourages the need to conduct research regarding what investors or potential investors consider when making decisions. Previous research shows the need to use primary data that not only includes rational and irrational factors, but also considers accounting information, both internal and published to external parties. The current research aims to prove whether financial slack and voluntary reporting will support stock investment decisions made by young investors. An experimental research witH2x2between-subjects design is conducted to provide empirical support regarding the usefulness of internal and external information in stock investment decisions. The sample was 93 undergraduate students majoring in Accounting who had at least taken or were currently taking courses related to Stock Investment. Some of them are regular visitors to the Investment Clinic from the Business Faculty in Surabaya. Sixty-three data from participants who successfully answered the manipulation check questions were processed to answer the research hypothesis. The statistical tool analysis of variance is used to test the hypothesis. Research findings show that financial slack was not influencing stock investment decisions, while voluntary reporting in the form of Sustainability Reporting is proven to influence stock investment decisions of young participants. Another result is the interaction effect of financial slack and voluntary reporting on stock investment decisions, which shows the importance of disclosure about the use of slack resources because it will influence investor decisions